Awareness and readiness on Quantum Communication Technology among the regulators, industry players and academicians in Malaysia - Shahrul, Nur Sabrina; Mohd Hanefah, Mustafa; Masruki, Rosnia; Yaakub, Nor Asiah; Mohamad, Noorihsan (Global Academic Excellence (M) Sdn Bhd (GAE), 2024)
The Quantum Communication Technology (QCT) industry is growing aggressively at the global level, but the implementation of this technology is not yet clear in Malaysia. This qualitative study reviews the awareness and readiness among regulators, industry players and an academia on development of QCT in Malaysia. This study conducted a focus group discussion involving twelve experts representing regulators, industry players and academicians who have extensive background and knowledge in cybersecurity. This study found that most of the respondents have basic understanding on the QCT and they are also aware on the and QCT development. In this study, respondents demonstrated varying levels of awareness of Quantum Communication Technology (QCT), with 8 out of 12 having prior knowledge. The study emphasizes the need for enhanced education and promotion in Malaysia to foster QCT adoption across sectors. Themes further explore the challenges of QCT implementation, particularly the high cost and evolving cybersecurity landscape. Recommendations include government involvement, cost-benefit analyses, continuous cybersecurity improvement, and top-down support to ensure successful QCT integration, especially in the telecommunications sector, where the high-cost poses challenges. The study underscores the significance of education, government collaboration, and financial support for effective QCT implementation in Malaysia.